2000
DOI: 10.1038/sj.bdj.4800750
|View full text |Cite
|
Sign up to set email alerts
|

Patients with cardiac disease: considerations for the dental practitioner

Abstract: The provision of dental treatment under both local anaesthesia and sedation has an excellent safety record, although medical problems may occur. The high prevalence of cardiac disease in the population, particularly ischaemic heart disease, makes it the most common medical problem encountered in dental practice. Additionally, the increasing survival of children with congenital heart disease makes them a significant proportion of those attending for dental treatment. While most dental practitioners feel confide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 21 publications
1
29
0
7
Order By: Relevance
“…Also the finding that many felt less confident when treating children with CHD compared with treating otherwise healthy children is in accordance with the literature . The finding that a quarter of the dentists in the present study responded that they used more treatment time with CHD patients compared with healthy children might be an additional facet of the same insecurity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Also the finding that many felt less confident when treating children with CHD compared with treating otherwise healthy children is in accordance with the literature . The finding that a quarter of the dentists in the present study responded that they used more treatment time with CHD patients compared with healthy children might be an additional facet of the same insecurity.…”
Section: Discussionsupporting
confidence: 90%
“…This means that a significant number of children and adolescents with CHD are taken care of in dental practice. It is therefore a reason for concern that studies have revealed that dentists feel uncertain and insecure about treatment for children with CHD . Parents of children with severe CHD have also reported to be less satisfied with their reception at public dental clinics compared with the parents of healthy children .…”
Section: Introductionmentioning
confidence: 99%
“…Nach einem Herzinfarkt oder dem Einsetzen eines Herzklappenersatzes sollten chirurgische Eingriff e innerhalb des 1. Jahres nur nach strenger Indikationsstellung erfolgen [10]. Bei einigen Patienten kann eine Dauertherapie mit Antikoagulantien zur Verhinderung thromboembolischer Komplikationen indiziert sein [6].…”
Section: Kardiovaskuläre Erkrankungenunclassified
“…1 , 2 This can lead to infection of sterile vegetations on cardiac valves in susceptible patients to endocarditis. 3 Fiehn et al 4 showed that in patients with infectious endocarditis, Streptococci strains isolated from the blood sample were similar to bacteria collected from the oral cavity. …”
Section: Introductionmentioning
confidence: 99%